Pengaruh Persepsi Self Esteem dan Locus Of Control terhadap Kinerja Karyawan melalui Kepuasan Kerja - Isna Asdiani Nasution; H Hafizah; Tiarahayu Tiarahayu Pridhisty (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2022)
This study aims to determine the effect of perceptions of self-esteem and locus of control on employee performance through job satisfaction at PT. PLN (Persero) UIP3B Sumatera UPT Medan. Path analysis research design is used as an analytical tool to determine the direction of the variables studied and to justify how significant the influence of the independent and dependent variables is either directly or indirectly through the mediating variable. In this study, the entire population sampled was 130 employees at PT. PLN (Persero) UIP3B Sumatera UPT Medan. The results of this study indicate that the self-esteem variable has a positive and significant effect on job satisfaction. Locus of control has a positive and significant effect on job satisfaction. Self-esteem has a positive and significant effect on employee performance. Locus of control has a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance. Job satisfaction is able to mediate the effect of self-esteem on employee performance. Job satisfaction cannot mediate the locus of control effect on employee performance.